Panggung Depan dan Panggung Belakang TikToker Remaja Denpasar sebagai Wujud Identitas di Media Sosial - Agustina, Ni Made Dwi; Suka Arjawa, I Gst. Pt. Bagus; Sastri Mahadewi, Ni Made Anggita (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2022)
The Dramaturgy concept in this study states that TikToker is an actor who plays theatrical stage. The social life of TikToker as an actor who plays a stage plays is divided into front stage and back stage. The front stage TikToker of Denpasar’s teenage, namely the situation when they present content on social media according to their identity. Tiktoker is an identity which made a formal role that shown by content on social media, for example role as a model, astrologer, traveller, also dancer. Then, the backstage of TikToker of Denpasar’s teenage, which is the situation when they are outside the front stage. Furthermore, TikToker after realizing their identity on social media brings a social impact, as a form of activiy that is able to influence others in the perspective Dramaturgy. The social impacts are divided into expected social impacts and unexpected social impacts.